The oldest Calosargus Mostovski, 1997 from the Middle Jurassic of China (Diptera: Brachycera: Archisargidae) - Zhang, Kuiyan; Yang, Ding; Ren, Dong; Shih, Chungkun (Zootaxa, 2007)
The family Archisargidae is an endemic Jurassic group. So far, 23 described species in 8 genera have been found in Kazakhstan, China and Mongolia. Calosargus Mostovski, 1997 is a small genus with 2 subgenera and 3 species from the Middle/Upper Jurassic of Kazakhstan. In this paper, 6 new species from the Middle Jurassic of China that belong to Calosargus (Calosargus) are described. They are the oldest known members in this genus. A key to the species of the genus Calosargus is given.